2013
DOI: 10.1186/1752-0509-7-s6-s12
|View full text |Cite
|
Sign up to set email alerts
|

Missing value imputation for microarray data: a comprehensive comparison study and a web tool

Abstract: BackgroundMicroarray data are usually peppered with missing values due to various reasons. However, most of the downstream analyses for microarray data require complete datasets. Therefore, accurate algorithms for missing value estimation are needed for improving the performance of microarray data analyses. Although many algorithms have been developed, there are many debates on the selection of the optimal algorithm. The studies about the performance comparison of different algorithms are still incomprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 48 publications
0
24
0
1
Order By: Relevance
“…They use the Average Distance Between Partition (ADBP) to calculate clustering error, and they show that BPCA, LLS, and kNN give similar clustering results. Chiu et al find that LLS-like algorithms performed better than kNN-like algorithms in terms of downstream clustering accuracy (measured using cluster pair proportions) [31]. De Souto et al evaluate whether the effect of different imputation methods on clustering and classification are statistically significant [32].…”
Section: Imputation With Clustered Datamentioning
confidence: 99%
“…They use the Average Distance Between Partition (ADBP) to calculate clustering error, and they show that BPCA, LLS, and kNN give similar clustering results. Chiu et al find that LLS-like algorithms performed better than kNN-like algorithms in terms of downstream clustering accuracy (measured using cluster pair proportions) [31]. De Souto et al evaluate whether the effect of different imputation methods on clustering and classification are statistically significant [32].…”
Section: Imputation With Clustered Datamentioning
confidence: 99%
“…A variety of reasons involve for missing values in GE data such as corruption of image, scratches on the slides, poor hybridization, inadequate resolution, fabrication errors and so on (Schuchhardt et al 2000, Tuikkala et al 2006. Microarray GE datasets typically contain 1-10% missing values that could affect up to 90% of genes (Chiu et al 2013). On the other hand, outliers may also occur in GE datasets due to different steps of data generating process from hybridization to image analysis for various reasons (Shahjaman et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Filling missing values with zeros or with the row average is a simple imputation strategy, but it is far from optimal. Therefore, many advanced algorithms have been developed to impute the missing values in microarray data [1012]. The existing algorithms can be divided into four categories [11]: global approach, local approach, hybrid approach and knowledge-assisted approach.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the need, we previously developed a performance comparison framework [12] which provides 13 testing microarray datasets, three types of performance indices, 9 existing algorithms, and 110 runs of simulation. We found that no single algorithm can perform best for all types of microarray data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation